1995
DOI: 10.1073/pnas.92.9.3834
|View full text |Cite
|
Sign up to set email alerts
|

The photoreceptor sensory rhodopsin I as a two-photon-driven proton pump.

Abstract: Proton translocation experiments with intact cells of Halobacterium salinarium overproducing sensory rhodopsin I (SRI) revealed transport activity of SRI in a two-photon process. The SRI amino acid sequence (9) reveals a striking degree of sequence homology to BR (10) and HR (11), suggesting seven transmembrane helices (A-G) as found for BR (12) and HR (13). Retinal is bound as a protonated Schiff base (14,15) to Lys-206 in helix G of SRI. In BR Asp-85 and Asp-96 function as proton acceptor and donor, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
(41 reference statements)
2
26
0
Order By: Relevance
“…In the absence of HtrI, the SRI protein shows slow proton pumping via the retinal Schiff's base (Bogomolni et al 1994). This result suggests that the photochemical cycle undergone by the SR proteins may normally result in a Schiff's base deprotonation-reprotonation reaction similar to that shown by bacteriorhodopsin (BR), but that the presence of HtrI prevents the release of protons to the aqueous phase (Haupts et al 1995). Instead, HtrI presumably undergoes a conformational change by either electrostatic or allosteric coupling and this results in a photoresponse.…”
Section: Halobacteriamentioning
confidence: 81%
“…In the absence of HtrI, the SRI protein shows slow proton pumping via the retinal Schiff's base (Bogomolni et al 1994). This result suggests that the photochemical cycle undergone by the SR proteins may normally result in a Schiff's base deprotonation-reprotonation reaction similar to that shown by bacteriorhodopsin (BR), but that the presence of HtrI prevents the release of protons to the aqueous phase (Haupts et al 1995). Instead, HtrI presumably undergoes a conformational change by either electrostatic or allosteric coupling and this results in a photoresponse.…”
Section: Halobacteriamentioning
confidence: 81%
“…In the blue species ( max 587 nm) Asp-76 is protonated, and in the purple species ( max 552) Asp-76 is unprotonated. In HtrI-free SRI, the pK a of Asp-76 is 7.2-7.4 (6,8). Binding of full-length HtrI, in addition to blocking the SRI cytoplasmic channel, increases this pK a of Asp-76 to 8.6 -8.9 (25).…”
Section: Resultsmentioning
confidence: 98%
“…The capability of SRI to pump protons has been studied in greater detail (5)(6)(7)(8). Olson et al (5) and Bogomolni et al (6) demonstrated that the proton transfer is driven by orange light in a single photon process.…”
Section: Discussionmentioning
confidence: 99%
“…Haupts et al (7,8) performed similar experiments with intact cells and, additionally, analyzed photocurrents of SRI containing membranes attached to the black-lipid membrane. From their results, the authors concluded that the proton transfer is based on a two-photon process in which the S 373 -intermediate absorbs a ''blue'' photon to short-cut the photocycle.…”
mentioning
confidence: 99%